Book Review: Humanitarian Intervention: An Inquiry Into Law And Morality By Fernando R Teson - Zan, Myint (Journal of Malaysian and Comparative Law, 2019)
Even though Fernando R Teson's book Humanitarian Intervention: An Inquiry Into Law And Morality (hereinafter referred to as "Teson") was first published in 1988 it is eminently suitable for review nowadays due to a multiplicity of reasons. First, issues concerning the use of force and human rights have come to the fore, even more prominently in present times than it was in 1988.